Optimation economic order quantity method for a support system reorder point stock - Linda Perdana Wanti; Ratih Hafsarah Maharrani; Nur Wachid Adi Prasetya; Eka Tripustikasari; Ganjar Ndaru Ikhtiagung (Institute of Advanced Engineering and Science, 2020)
The success of a company is measured by the ability to provide goods and services at the right time and place. Besides, one of the factors of the company's progress is also supported by inventory management which functions to control the company's inventory by neither hoarding lots of products nor running out of products. The development of technology requires a company's inventory management that is fast, precise and accurate to support its’ performance. In fact, some companies have difficulty in determining the stock of their goods production so that it impedes the fulfillment of consumer needs in the event of high market demand. This study is to determine the reorder point stock of a company that determines the number of purchases and sales of the company's products, therefore the amount of expenses and income can be presented to the board of directors to be followed up quickly and accurately. The method used is a statistical approach to the economic quantity model where safety stock analysis is first performed. This method is used to put the company's products to the inventory so that there are no excess or even shortages of products. System development method used is a user centered design, which is the most suitable to the study. The output of the activity is information in the form of advice to the company leaders in making decisions about production planning, controlling stock inventory, detailing market demand quickly, precisely and accurately and developing a decision support system that is made by taking into account the details of user needs.